Pump-probe study of atoms and small molecules with laser driven high order harmonics - Cao, Wei (Kansas State University, 2014)
A commercially available modern laser can emit over 10^15 photons within a time window of a few tens of femtoseconds (10^-15 second), which can be focused into a spot size of about 10 um, resulting in a peak intensity above 10^14 W/cm^2. This paves the way for table-top strong field physics studies such as above threshold ionization (ATI), non-sequential double ionization (NSDI), high order harmonic generation (HHG), etc.. Among these strong laser-matter interactions, high order harmonic generation, which combines many photons of the fundamental laser field into a single photon, offers a unique way to generate light sources in the vacuum ultraviolet (VUV) or extreme ultraviolet (EUV) region. High order harmonic photons are emitted within a short time window from a few tens of femtoseconds down to a few hundreds of attoseconds (10^-18 second). This highly coherent nature of HHG allows it to be synchronized with an infrared (IR) laser pulse, and the pump-probe technique can be adopted to study ultrafast dynamic processes in a quantum system. The major work of this thesis is to develop a table-top VUV(EUV) light source based on HHG, and use it to study dynamic processes in atoms and small molecules with the VUV(EUV)-pump IR-probe method. A Cold Target Recoil Ion Momentum Spectroscopy (COLTRIMS) apparatus is used for momentum imaging of the interaction products. Two types of high harmonic pump pulses are generated and applied for pump-probe studies. The first one consists of several harmonics forming a short attosecond pulse train (APT) in the EUV regime (around 40 eV). We demonstrate that, (1) the auto-ionization process triggered by the EUV in cation carbon-monoxide and oxygen molecules can be modified by scanning the EUV-IR delay, (2) the phase information of quantum trajectories in bifurcated high harmonics can be extracted by performing an EUV-IR cross-correlation experiment, thus disclosing the macroscopic quantum control in HHG. The second type of high harmonic source implemented in this work is a single harmonic in the VUV regime (around 15 eV) filtered out from a monochromator. Experiments on D_2 molecules have been conducted using the 9th or the 11th harmonic as the pump pulse. Novel dissociative ionization pathways via highly excited states of D_2 have been revealed, thus suggesting potential applications for time-resolved studies and control of photochemistry processes.
Keywords: High harmonic generation; COLTRIMS; Ultrafast dynamics; Pump-probe; Atomic Physics (0748); Optics (0752)